2020
DOI: 10.1177/1758835919888999
|View full text |Cite
|
Sign up to set email alerts
|

The impact of progesterone receptor expression on prognosis of patients with rapidly proliferating, hormone receptor-positive early breast cancer: apost hocanalysis of the IBIS 3 trial

Abstract: Background: In the Italian Breast Cancer Intergroup Studies (IBIS) 3 phase III trial, we compared cyclophosphamide, methotrexate, 5-fluorouracil (CMF) alone to sequential epirubicin/CMF regimens in patients with rapidly proliferating early breast cancer (RPEBC). We performed a post hoc analysis in the subgroup of patients with hormone-receptor-positive RPEBC on the prognostic role of progesterone receptor (PgR) status. Methods: RPEBC was defined by thymidine labeling index (TLI) >3% or grade 3 or S-phase &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In study of Bracvaccini et al only PR status in early luminal breast cancer was associated with OS and DFS among biological features. Namely, when the cutoff of PR was either <10% or <20% the patients had 5-and 10-years OS rates of 92% and 80%, respectively, compared with 95% and 89% for PR >10% [27]. Another study showed that PR expression in ER-positive early Luminal A was a significant independent prognostic factor and the difference of prognosis between PR-positive and PR-negative tumors became evident more than 5 years after surgery, resulting in better prognosis in PR-negative than in Luminal B type [16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In study of Bracvaccini et al only PR status in early luminal breast cancer was associated with OS and DFS among biological features. Namely, when the cutoff of PR was either <10% or <20% the patients had 5-and 10-years OS rates of 92% and 80%, respectively, compared with 95% and 89% for PR >10% [27]. Another study showed that PR expression in ER-positive early Luminal A was a significant independent prognostic factor and the difference of prognosis between PR-positive and PR-negative tumors became evident more than 5 years after surgery, resulting in better prognosis in PR-negative than in Luminal B type [16].…”
Section: Discussionmentioning
confidence: 98%
“…PR expression and Ki-67 using IHC are important prognostic factors in ER-positive early luminal breast cancers, which suggests PR's utility as a marker for differentiation between Luminal A and Luminal B subtypes [24]. The studies showed that lack of PR expression is significantly associated with poorer prognosis in luminal breast cancers [27], independently of other factors [28], and PR-positive breast cancer had a better prognosis with regard to OS and DFS [24].…”
Section: Discussionmentioning
confidence: 98%
“…At present PgR status is not considered to confer selective advantage between EHT types 45 and ER status remains the only factor predictive of tamoxifen benefit 46 . However, the absence of this synergistic response to EHT and relative endocrine resistance is a possible explanation for the worse outcomes associated with PgR- disease 14–16 , 21 , 43 , 44 , 47 . Given these data, perhaps conscious consideration should be given to novel therapeutic strategies when treating patients with the PgR- subtype, particularly in cases of HER2- disease where the option of targeted anti-HER2 therapy or systemic chemotherapy may not be clinically indicated 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ER is a good prognostic marker of clinical outcome in breast cancer and a useful predictive marker of response to adjuvant therapy (Louie and Sevigny, 2017). PR expression is also an independent valuable prognostic biomarker in breast cancer, and its expression level must be taken into account when deciding on adjuvant treatments in patients with hormone-receptor-positive early breast cancer (Bravaccini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%